Landscape planning: Sustainable practices, design and urban development - Cilek, Ahmet; Unal, Muge (Nova Science Publishers Inc., 2025)
This book presents a comprehensive examination of innovative methodologies and strategies for landscape architecture, urban planning, and sustainable development. Through ten meticulously researched chapters, the volume explores topics ranging from landscape planning in ecologically sensitive regions, such as the Altai, to enhancing urban ecological connectivity, developing greenway systems, and applying statistical methods in landscape research. Each chapter elucidates cutting-edge approaches to balancing environmental sustainability with urbanization challenges, rendering the book valuable to professionals and academics. The case studies encompass diverse geographical contexts, including urban centers in Turkey, greenway systems in the United States, and cultural landscapes in historical urban areas. Key concepts such as land-use zoning, ecological connectivity, urban green spaces, and the use of the Normalized Difference Vegetation Index (NDVI) in mapping have been thoroughly explored, with a particular focus on promoting sustainable socio-economic development and conservation efforts. Ideal for landscape architects, urban planners, and environmental researchers, this book advances theoretical understanding and provides practical insights into integrating ecological planning with urban growth. Addressing the pressing need for sustainable urban environments equips readers with tools to navigate the complex intersection between nature and human development. © 2025 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Conservation; Ecodesign; Ecology; Economics; Green development; Green economy; Land use; Natural environment; Sustainable development; Comprehensive examination; Design development; Ecological connectivities; Greenways; Innovative methodologies; Innovative strategies; Landscape architecture; Landscape planning; Sustainable practices; Urban development; Urban growth